2016
DOI: 10.1186/s12931-016-0431-7
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory symptoms, sleep-disordered breathing and biomarkers in nocturnal gastroesophageal reflux

Abstract: BackgroundNocturnal gastroesophageal reflux (nGER) is associated with respiratory symptoms and sleep-disordered breathing (SDB), but the pathogenesis is unclear. We aimed to investigate the association between nGER and respiratory symptoms, exacerbations of respiratory symptoms, SDB and airway inflammation.MethodsParticipants in the European Community Respiratory Health Survey III in Iceland with nGER symptoms (n = 48) and age and gender matched controls (n = 42) were studied by questionnaires, exhaled breath … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 34 publications
3
31
0
4
Order By: Relevance
“…The severe obesity found in women with asthma might interact with OSA pathogenesis (Alkhalil, Schulman, & Getsy, 2009;Prasad, Nyenhuis, & Weaver, 2014). OSA is associated with huge variations in intrathoracic pressure, especially in obese patients, increasing the burden of gastroesophageal reflux (Emilsson et al, 2016), which in turn can promote asthma symptoms. Although the use of proton pump inhibitors was higher in asthmatic than in non-asthmatic patients, no relationship was found between use of such medications and OSA severity in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The severe obesity found in women with asthma might interact with OSA pathogenesis (Alkhalil, Schulman, & Getsy, 2009;Prasad, Nyenhuis, & Weaver, 2014). OSA is associated with huge variations in intrathoracic pressure, especially in obese patients, increasing the burden of gastroesophageal reflux (Emilsson et al, 2016), which in turn can promote asthma symptoms. Although the use of proton pump inhibitors was higher in asthmatic than in non-asthmatic patients, no relationship was found between use of such medications and OSA severity in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…У сучасній медичній літературі широко обговорюються причини патогенезу кардіоваскулярних ускладнень при синхронному перебігу ОАС та ГЕРХ [6,7]. Серед основних чинників, науковці відзначають активацію симпато-адреналової та ренін-ангіотензинової систем в наслідок розвитку гіпоксемії [8], наявність спільних ланок інервації стравоходу і серця [9].…”
Section: вступunclassified
“…Розвиток кардіоваскулярних ускладнень у хворих з поєднаним перебігом ОАС та ГЕРХ не підлягає сумніву [6,7]. Більше того, останнім часом з'являється все більше досліджень, в яких автори констатують вірогідну асоціацію між ОАС, ГЕРХ та смертністю від фатальних серцевих аритмій, ішемії міокарда, мозкового інсульту.…”
Section: обговорення результатів дослідженняunclassified
“…Nocturnal gastroesophageal reflux (nGER) has been reported to have negative effect on sleep quality, emotions, and work productivity of the patients. Moreover, nGER is considered to be related to bronchitis and asthma and may aggravate respiratory symptoms . A previous study by Shaker et al included 1000 patients with reflux symptoms and demonstrated that 79% of the participants had prevalent nocturnal heartburn .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nGER is considered to be related to bronchitis and asthma and may aggravate respiratory symptoms . A previous study by Shaker et al included 1000 patients with reflux symptoms and demonstrated that 79% of the participants had prevalent nocturnal heartburn . Two‐thirds of participants who experienced heartburn at least thrice per week were more likely to remain awake or to wake up at night due to reflux symptoms …”
Section: Introductionmentioning
confidence: 99%